Diet Quality, Gut Microbiome and Metabolism. (7th June 2021) - Bagheri, Minoo; Mosley, Jonathan D; Ferguson, Jane F
Abstract: Objectives: Dietary pattern is associated with circulatory and gut metabolome variation. However, it is unclear if this association is mediated by gut microbiome composition. We investigated whether the interaction between diet quality and gut microbiome influenced circulatory and gut metabolites. Methods: We conducted a cross-sectional study among 75 healthy adults in the ABO Study. Diet quality was assessed using the Healthy Eating Index (HEI). Metabolome profiling (800 circulatory and 767 gut metabolites) was performed at Metabolon Inc. Two gut microbiome Enterotypes (1 and 2) were identified using the Partitioning Around Medoids method. Metabolite set enrichment analysis was performed using Metaboanalyst 4.0. Multivariable linear regression was conducted to test for an interaction between the gut microbiome-HEI and metabolite levels. Results: Diet quality was significantly higher in participants with Enterotype 2, compared to those with Enterotype 1 ( P  = 0.01). The gut microbiome-HEI interaction (Enterotype 2 and higher HEI) was directly related to omega-3/omega-6 poly-unsaturated fatty acids (PUFAs) and acetyl/acyl derivatives of amino acids. It was inversely linked to polar lipids including 1-palmitoyl-2-linoleoyl-GPC (16:0/18:2), which demonstrated the most significant association (β = 0.008, P  = 0.0009) among circulatory metabolites. Considering gut metabolome, however, the interaction directly associated with metabolites involved in DNA synthesis including thymidine 5′-monophosphate, which showed the strongest association (β = 0.041, P  = 0.0007), and bile acids derivatives. It inversely associated with fatty acids and branch chain amino acids. 'Glycine and serine metabolism' was the only pathway that was significantly enriched by the interaction ( P  = 0.044). Conclusions: Future research is warranted; however, these findings suggest that the efficacy of dietary interventions targeted at altering metabolism (the metabolism of lipids (PUFAs and polar lipids), amino acids and nucleotides) may be dependent on gut microbiome composition. Funding Sources: The National Institutes of Health.